A study on the factors that influence the employability of fresh graduates in Malaysia / Farah Zulaika Nordin and Fatin Ameera Ab Razak - Nordin, Farah Zulaika; Ab Razak, Fatin Ameera (Faculty of Business and Management, 2015)
In Malaysia, the rate of unemployment among fresh graduates is high since many graduates are found lacking of what are needed to acquire and maintain their jobs. The objective of this study is to determine the factors that influence the employability of fresh graduates in Malaysia. The independent variables of this research consist of interpersonal skills and personality. They are 100 respondents from public and private companies in Gombak, Selangor. All independent variables show positive relationship towards the dependent variables. This study refers to primary data for supporting the sampling technique. Meanwhile, the researchers used questionnaires as the method to collect all the data from the 100 respondents in completing the research objective. Plus, the data of this study, was analyzed and interpreted into readable and informative data through Reliability Analysis, Descriptive Analysis and Pearson’s Correlation. The result of the study shown in this research completely agrees that interpersonal skills and personality had influence employability of fresh graduates in Malaysia. In addition, personality are the most influence factor to employability of fresh graduates in Malaysia.